An analysis on thematic progression patterns of reading comprehension TOEFL prediction texts - Sinaga, Dwi Pebrina; Harahap, Nurul Husnah; Tampubolon, Marlina (Institute of Computer Science (IOCS), 2024)
The importance of learning English, a global language, is immense. With the rising trend of English-medium preschools, driven by parents' desire for their children to achieve native-like proficiency, English has become a priority for many students. BSC Education outlines several reasons for this: English's global prevalence facilitates cross-border communication, enhances job prospects, and improves social interactions. It is also the dominant language in academia, media, and the internet. To assess proficiency, students often take the Test of English as a Foreign Language (TOEFL), which evaluates speaking, listening, reading, and writing skills. TOEFL scores are essential for admission to English-medium educational institutions. Despite its importance, reading comprehension can be challenging, particularly under time constraints, as students must understand texts and answer questions accurately and quickly. Mastering reading skills is thus crucial for TOEFL success. This research focuses on analyzing TOEFL prediction reading texts by examining thematic progression patterns and dominant themes. Understanding these patterns can help students improve their reading comprehension strategies, better preparing them for the TOEFL exam. Additionally, the research offers valuable insights for writing scientific texts, providing a useful reference for students aiming to enhance their academic writing skills.